EFFECTIVE WAYS OF TEACHING IDIOMS TO ESL STUDENTS - Sabina Ro'ziyeva Sanoqul qizi (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Annotation. This article explores effective strategies for teaching idioms to English as a Second Language (ESL) students. Idioms pose a unique challenge for language learners due to their figurative nature, cultural context, and varied usage. The study employs a comprehensive approach, incorporating literature analysis and practical methods to enhance idiom comprehension among ESL learners. The results highlight the efficacy of these methods in fostering a deeper understanding of idiomatic expressions. The discussion section delves into the implications of the findings, offering insights into the broader context of ESL teaching, and the article concludes with suggestions for future research and classroom application.